WUJUD ALIH KODE DALAM MASYARAKAT TUTUR KONJO DI SINJAI - Herawati Herawati (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
Bilingual or multilingual speakers are often code-switch from one language to another, especially when two or more languages are used in the environment. This article explores the potential theoretical explanations for this language behavior and the role of language dominance in the direction of switch. The data consists of primary and secondary data. The primary data were collected from daily speech events in the various domains. The secondary data is any information other than the primary data which support the primary data. In short, code-switching follows the functional and the grammatical principles and is a complex, rule-governed phenomenon. The use of Buginese language (BDS), Malayic-Buginese language (DMB), and Indonesian language (BI) have led to the functional elaboration of all language beside Konjo language (BK) in the Konjo speech community in Sinjai. There are some factors governing the code-switching process in the Konjo speech community in Sinjai. They are: (1) the language abilities of the speaker and the addressee, (2) the setting and the situation, both official and non-official, (3) the participants in the interaction, and (4) the aim of the speech act.